The underwater dig : an introduction to marine archaeology - Marx, Robert F. (New York : H. Z. Walck, 1975)
An introduction to underwater archaeology for the amateur, including the history, principles, techniques, importance, and future of this field.
Includes index.
Bibliography: p. [230]-242.
Keywords: Underwater archaeology; Underwater archaeology